PENGARUH PENGEMBANGAN KARIR, IKLIM ORGANISASI DAN SELF EFICACY TERHADAP KEPUASAN KERJA PEGAWAI BADAN KEPEGAWAIAN DAERAH PROVINSI RIAU - Bangun Murgabe; Dewita Suryati Ningsih; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in the are of staffing (BKD) Riau Province Jl. Cut Nyak Dien Pekanbaru. The purpose of this research is to know the influence of career development, organizational climate and self efficacy against partially employee job satisfaction and simultaneous on the Staffing Agency Area (BKD) Riau Province as well to find out which variables are the most significant influence on job satisfaction employees on Staffing Agency Area (BKD) Riau Province. The population of the research was 69 employees at the Staffing Agency Area (BKD) Riau Province with model census sampling. Variable used is the research career development, organizational climate and self eficacy as independent variable and job satisfaction of employees as the dependent variable. Methods of data analysis using multiple linear regression analysis was aided by 20 SPPS of windows. The results of this study concluded that variables career development, organizational climate and self partially and simultaneous efficacy have significant influence towards job satisfaction employees of Staffing Agency Area (BKD) Riau Province. Where is the most dominant factors influencing job satisfaction factor is climate of the organization. The research that has been conducted in accordance with the regression test (t test) and (test f) shows the free variable examined is variables examined is variable for career development, organizational climate and self eficacy have significant influence towards the dependent variable employee job satisfaction.Keywords : career development, organizational Climate and Self Efficacy and Job Satisfaction